The thermodynamics of binary liquid mixtures - Scoones, Brett Warren Hamilton (Rhodes University, Faculty of Science, Department of Chemistry, 1983)
A systematic study of the excess thermodynamic properties of two-ring compounds and n-alkanes was conducted. The excess enthalpies were determined at 288,15 K and 298,15 K by using a flow microcalorimetric technique. The excess volumes of tetralin and cycloalkanes, and tetralin and --alkans at 288,15 K and 298,15 K were determined by using a vibrating tube densitometer. The results showed trends relating to the size and shape of the n-alkane and cycloalkan molecules. The theory developed by Flory was applied to the decalin + cycloalkane and + n-alkane systems and this gave qualitative predictions of the excess enthalpies from the excess volumes and vice versa.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Thermodynamics; Thermodynamics -- Tables; Solution (Chemistry); Liquids